Evasão escolar na pandemia da COVID-19: o que os adolescentes nos ensinam - Andréa Chicri Torga Matiassi (2022)
This research entitled "School evasion in the COVID-19 pandemic: what adolescents teach us" presents an investigation into the school evasion (drop-out) of teenagers students, who were in elementary or high school, and were considered by the schools as students who had broken with the schooling process, considering the teenagers' viewpoint as subject and the aspects of his/her subjectivity that may have (or not have) interfered with the evasion. It was possible to verify, from an analysis of the literature produced on the subject of school dropout, that both factors, internal and external to the school, are pointed out as the causes of school dropout. Among the main ones are: work for male adolescents and pregnancy for female adolescents, considering also the lack of interest for both sexes. Some studies emphasize the problem of school failure as one of the main causes of dropping out, while others focus on the student's history of retention. However, the particularities of adolescence are also presented as fundamental hypotheses interfering with the observable loss of interest in studies at this life moment. If there is a possible rupture of the adolescent with school, this should not be analyzed disregarding the relationship of the subject that drops out with school. In this sense, aiming to listen to what the adolescents have to say about school dropout, we opted for a psychoanalytic-oriented methodology, as well as the diagnostic conversations, used by research/intervention, developed by the Interdisciplinary Center for Research in Psychoanalysis and Education (NIPSE). Conversations were conducted with principals, coordinators, teachers, and students at two government schools in the Belo Horizonte city. In addition to the conversations, interviews were conducted with six adolescents considered by the school to be "truant" students. With psychoanalytic methodology and its theoretical contributions, we intended to differentiate, among the causes identified for school dropout, those that show school as the main factor of failure, from those that indicate elements of the subjectivity of the adolescent. The research field took place during the pandemic and was crossed by it, which produced changes in the methodologies used, as almost all conversations and interviews had to be conducted at a distance. The interventions made it possible to: (a) to verify how school dropout had always been present in the schools researched, but with the pandemic it worsened; (b) to show how distance education generated deadlocks and the teacher disappearance as a figurehead, seriously affecting the teaching and learning process; (c) to learn from the adolescents about the mismatch produced between the discourses of education professionals and the adolescents themselves, and (d) how the closure of schools, due to the pandemic, provided adolescents with a return to the role of the teacher as Other, necessary in the process of schooling and crossing of adolescence.